+0  
 
0
50
5
avatar

Let a and b be the roots of x^2 - 23x + 47 = 0.  Compute (a - 1)(b - 1).

 Sep 7, 2020
 #1
avatar+26951 
+1

Answer: 

( from Quadratic Formula)

𝑥=23/2±Sqrt (341) / 2   You can do the rest    

 Sep 7, 2020
 #2
avatar
+1

NO! Don't do that @ElectricPavlov!

 

\((a-1)(b-1)=ab-(a+b)+1\)

 

The product of the roots is 47/1=47, and the sum of the roots is 23/1=23. So the answer is 47-23+1=25.

 Sep 7, 2020
 #4
avatar+230 
+2

Great solution guest! 

Ericthegg123  Sep 7, 2020
 #5
avatar+26951 
+1

Definitely easier!smiley

ElectricPavlov  Sep 8, 2020
 #3
avatar+230 
+2

From the equation x^2-23x+47=0 we apply the quadratic formula:

23±sqrt(529-188)/2

=2±sqrt(341)/2

The value of a and b are: 2+sqrt(341)/2 and 2-sqrt(341)/2, you should be able to take it from here.laugh

 Sep 7, 2020

37 Online Users

avatar